Recycling perception and practice in Shah Alam municipality: article - Azmi, Norazrina; Syed A Kadir, Sharifah Aisyah; Alias, Azil Bahari (2018)
Fast growth in the populace, development and technology has caused the increasing sum of municipal solid waste in Malaysia. To overwhelm this issues, recycling is one of the effective ways. This research objectives are to evaluate the public perception and to analyse practices of recycling in the city of Shah Alam. By 2030, Shah Alam city council aims to achieve ‘Zero Waste’. Thus, with this view, a preliminary investigation is required to be done, which is the main focus of this research. A questionnaire was developed to determine perception and practice of recycling. The survey were being distributed manually and by spreading the link from google.docs to the Shah Alam’s residents. The data collected was analyzed using statistical analysis, minitab software. The result showed that, majority of the Shah Alam’s resident aware and believe that recycling is important. However, low participation of respondent’s on recycling practice despite the fact that high percentage of respondent is knowledgeable on how to recycle solid waste. In Shah Alam municipality, majority of respondents participate in recycling practice due to environmental concern, followed by convenient and economic incentives. Result of the survey showed that lack of awareness about the recycling program and very few educational program about recycling are two mains barriers to sustainable recycling in Shah Alam. This research study found that, more convenient location for bins is the most potential strategy to promote recycling activity. In conclusion, more public participation and awareness need to be held to in order to increase the recycling practice in Shah Alam.